Direct dating Paleo-fluid flow events in sedimentary basins - Yang, P.; Liu, K.; Li, Zhen; Rankenburg, Kai; McInnes, Brent I.A.; Liu, J.; Evans, Noreen (ELSEVIER, 2022)
Reconstructing fluid evolution history in old sedimentary basins is extremely challenging due to the prolonged evolution, lack of exact age constraints and absence of preserved fluids. By integrating in-situ calcite U–Pb dating, fluid inclusion analysis, measurements of major and trace elements and carbon‑oxygen‑strontium isotopes, and molecular composition analysis of petroleum, we have reconstructed the fluid evolution history during the Carboniferous in an Ordovician deeply-buried carbonate reservoir in the Tarim Basin, China, with unprecedented temporal resolution. Five generations of calcite cementation spanning over 37 m.y. are dated in a single calcite vein with U–Pb ages ranging from ~353 Ma to ~316 Ma. The initial cement was associated with an intrusion of hyper-saline brine, enriched in REEs. This was followed by influx of meteoric water to precipitate the second and third generations of cement, which are characterized by reduced salinity, anomalously high 87Sr/86Sr ratios and extremely low concentration of REEs. The fourth generation of calcite cement was formed in a deep-fluid system accompanied by oil charge as indicated by the presence of bitumen, oil inclusions and low δ13C and 87Sr/86Sr ratios. The fifth generation of cement was precipitated from equilibrated connate water, and has the lowest salinity and a comparable REE signature to the host rock. Oil charge event occurred around 326 Ma. This study demonstrates the effectiveness of combining in-situ calcite U–Pb geochronology, fluid inclusion analysis, elemental and isotopic geochemistry to elucidate high-resolution temporal fluid evolution in old sedimentary basins with a complex tectonic history, providing a new paradigm for studying geofluid evolution.